The Structural Conservation Problems of Traditional Houses in Eryeri, Mardin, Artuklu - Aktaş, Engin; Ercan Gündüz, Yasemin; Hamamcıoğlu Turan, Mine (01. Izmir Institute of Technology, 2023)
The aim of this study is to document the construction techniques, material usage, and structural failures of the traditional houses in a village of Mardin, Eryeri, in order to guide a conservation aimed development plan that will be prepared in the future and enhance the related rehabilitation implementations. Eight houses that have preserved their authenticity were selected. Field survey focusing on the structural elements such as foundations, walls, floors, and roofs was conducted with the conventional techniques of architectural restoration. Both failures and also alterations of the buildings were documented. The changes and alterations of the houses are documented. Visual analysis of the constructional qualities was made with Archicad23 tools. Comparison with the traditional houses in the vicinity was made with reference to data gathered via field survey, literature review and archive research. As a result, the traditional houses are integrated with the rocky terrain of the region and in masonry system. There is an intense use of local stone, Yellow Limestone. Vaults are common superstructure elements, but timber floor is also possible. The walls are stone masonry in all. The common structural problems are demolition of structural elements such as roofs. The causes of severe failures are neglect and natural aging. The reinforced concrete additions flanking to the authentic structures also cause failure. Within the scope of the conservation plan, it is important to prevent reinforced concrete annexes and to intervene the annexes that cause excessive loads urgently.

Çalışmanın amacı, Mardin ili Artuklu ilçesine bağlı Eryeri mahallesinde bulunan geleneksel yapım tekniklerini barındıran konutların yapım sistemlerini, malzeme kullanımlarını ve mevcut yapısal hasarlarını belgelemek, yapıların gelecekteki koruma uygulamalarını yönlendirecek planlama kararları için bir rehber oluşturmaktır. Özgünlüğünü ve bütünselliğini önemli oranda korumuş konutların yanı sıra, ağır hasarlı konutlar da incelenmiştir. Bu amaç doğrultusunda, arazi çalışmalarındaki incelemeler temel, duvar, döşeme ve çatı gibi yapı elemanları özelinde yapılmıştır. Yapıların geçirdiği değişimler ve dönüşümler aşamaları ile birlikte belgelenmiştir. Ayrıca bölgede yoğun kullanıma sahip olan tonoz tekniğinin Mardin ve çevresindeki kullanımı da incelenmiştir. Mardin ili ve çevresinde bulunan benzer yapım tekniklerini içeren tarihi yapılar ve köyler hakkında yapılmış olan öncü çalışmalar incelenmiştir. Yapım tekniklerinin yanı sıra bölgenin tarihi ve coğrafi özelliklerinin yapıların üzerindeki etkileri de araştırılmıştır. Eryeri mahallesinin oluşumu, gelişimi ve yerleşimi üzerine araştırmalar yapılmıştır. Konutların yapım sistemi yığma sistemdir, yapıların yığma duvarlarında ve tonoz üst örtülerinde yoğun olarak yöresel taş kullanımı söz konusudur. Yaygın yapısal sorunları yapısal elemanların kayıpları ile sonuçlanan yıkımlardır. Ağır hasarların nedeni bakımsızlık ve doğal yaşlanmadır. Ayrıca yapılara eklenen betonarme ekler de yapıların hasar derecelerinin artmasına neden olmaktadır. Koruma planlaması kapsamında betonarme eklerin önlenmesi, fazla yüke sebep olan eklere müdahalelerin acilen yapılması önemlidir.
Mardin, Artuklu, Eryeri'ndeki Geleneksel Evlerin Yapısal Koruma Sorunları
Thesis (Master)--İzmir Institute of Technology, Architecture, Izmir, 2023
Includes bibliographical references (leaves. 149-153)
Text in English; Abstract: Turkish and English
Keywords: Traditional houses; Conservation and restoration; Mardin houses; Traditional masonry structures; Preservation problems